Peningkatan Kreativitas Anak Menggunakan Media Loose Parts - Naomi Ifon Kafolamau; Maria Melita Rahardjo (Universitas Cokroaminoto Palopo, 2022)
This study aims to determine how loose parts media supports early childhood creativity, so that children can explore their imaginations using loose parts media. The method used is a descriptive qualitative method. Data collection techniques were carried out by direct interviews, making anecdotal notes, in-depth documentation studies and direct observations. Data analysis was carried out by observing video observations before carrying out research and video observations after carrying out research and analyzing anecdotal notes made during conducting research. The subjects in this study were children aged 4-5 years who took the Baby's Gym Kids City Ada Baru Salatiga class. the findings in this study are Play activities using removable media or loose parts carried out by researchers to find out how loose parts media support early childhood creativity greatly influences children's creativity, seen from the children's responses when they have played using removable media consisting of stones, leaves, twigs wood and pinecone. However, there are things that need to be considered by teachers when using this removable media as a medium for teaching materials, namely the teacher is able to provide instructions or provocation questions that provoke the imagination of children and the teacher also provides a concept lighter using story books as one of the media, where this media is very useful. help the teacher, because the children are very interested in story books so that when the teacher tells the story the children are very enthusiastic about listening to the story and even the children share their experiences. The role of the teacher in this case is very important where every activity takes place.